КРОВОСОСУЩИЕ КОМАРЫ (CULICIDAE) ПОДГОРНЫХ СТЕПЕЙ СЕВЕРНОГО ТЯНЬ-ШАНЯ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
As a result, research in the piedmont steppes waters of the Northern Tien Shan were found 21 species of mosquitoes. Analysis of the percentage of mosquitoes, showed that the dominant species were: Anopheles maculipennis, Aedes caspius caspius, Ae. dorsalis, Ae. flavescens, Ae. cyprius, Ae. vexans, Culex modestus, Cx. pipiens pipiens, Cx. p. molestus.